Liquidity risk premia in unsecured interbank money markets - Jens Eisenschmidt; Jens Tapking (European Central Bank (ECB), 2009)
Unsecured interbank money market rates such as the Euribor increased strongly with the start of the financial market turbulences in August 2007. There is clear evidence that these rates reached levels that cannot be explained alone by higher credit risk. This article presents this evidence and provides a theoretical explanation which refers to the funding liquidity risk of lenders in unsecured term money markets.
Keywords: G01; G10; G21; 330; 2007/2008 financial market turmoil; interbank money markets; Liquidity premium; unsecured lending; Geldmarkt; Bankenliquidität; Risikoprämie; Kreditderivat; Finanzkrise; Eurozone